2017
DOI: 10.1080/09286586.2017.1304562
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phosphate and Retinal Microvascular Changes: The Multi-Ethnic Study of Atherosclerosis and the Beaver Dam Eye Study

Abstract: Purpose Higher levels of serum phosphate are strongly linked to increased risk of cardiovascular disease and therapies aimed to lower serum phosphate are employed in the management of patients with chronic kidney disease (CKD). Data are limited, however, on serum phosphate as a risk factor for microvascular disease in community-based populations. It is important to determine the impact of novel risk factors, such as phosphate, on the microvasculature. Methods We conducted a prospective study of 3919 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…The persons randomized to the high-phosphate diet still had an average phosphate in the normal range (around 4 mg/dl). In larger community-living populations, Mehta et al reported an association between higher serum phosphate and prevalence of retinopathy, even among persons with a serum phosphate in the normal range in the Multi-Ethnic Study of Atherosclerosis, a finding confirmed in our study (30). In that study, serum phosphate was not associated with central retinal arteriolar or venular diameter; however, these measurements were made without flicker-light stimulation, thus this would only reflect the baseline diameter.…”
Section: Discussionsupporting
confidence: 82%
“…The persons randomized to the high-phosphate diet still had an average phosphate in the normal range (around 4 mg/dl). In larger community-living populations, Mehta et al reported an association between higher serum phosphate and prevalence of retinopathy, even among persons with a serum phosphate in the normal range in the Multi-Ethnic Study of Atherosclerosis, a finding confirmed in our study (30). In that study, serum phosphate was not associated with central retinal arteriolar or venular diameter; however, these measurements were made without flicker-light stimulation, thus this would only reflect the baseline diameter.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with other recent studies of modifiable exposures (e.g., nutrients in diet or bloodstream) and retinal vessel outcomes. [26][27][28] Although this observational study was not designed to identify a causal relationship between L/Z exposure and retinal vessel caliber, our findings support increasing evidence that carotenoids L/Z may have a role in modulating ocular blood flow, 11,12 in addition to their well-known antioxidant properties in the macula of the retina. 3,29 Although speculative, it is plausible that increased ocular blood flow may contribute to the protective associations observed for L/Z and macular pigment in observational studies, including protective associations observed for AMD.…”
Section: Discussionsupporting
confidence: 77%
“…The evidence shows that the increase of serum calcium might trigger the self‐regeneration cycle of ionized calcium influx and depolarization, resulting in increased retinal photoreceptor ellipsoid zone disruption in DR, leading to the impairment of retinal photoreceptor cell function and apoptosis 16,17 . Rupal et al 14 . and other scholars put forward that elevated phosphate has toxic effects on the vascular endothelium, which leads to retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence shows that the increase of serum calcium might trigger the self-regeneration cycle of ionized calcium influx and depolarization, resulting in increased retinal photoreceptor ellipsoid zone disruption in DR, leading to the impairment of retinal photoreceptor cell function and apoptosis 16,17 . Rupal et al 14 and other scholars put forward that elevated phosphate has toxic effects on the vascular endothelium, which leads to retinopathy. In vivo and in vitro studies have found that endothelial cells exposed to high phosphate concentration reduce the content of endothelial nitric oxide synthase, resulting in decreased vasodilation and vascular dysfunction 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation